PENGARUH LINGKUNGAN KERJA DAN PENGHARGAAN TERHADAP KREATIVITAS DAN KINERJA PEGAWAI DI UNIVERSITAS PENDIDIKAN GANESHA - Widhiastana, Nyoman Doddy; Wardana, Made; Sudibya, I Gde Adnyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The purpose of this research was to explain the influence of the work environment and reward for creativity and performance of employees at Ganesha University of Education. This research targeting all goverment employees in the Ganesha University of Education, but the number of questionnaires returned as many as 141 copies of a total of 253 employees. The data were analyzed using Partial Least Square (PLS). The results showed that (1)  work environment positive and significant impact on employee performance, (2) work environment positive and significant effect on creativity, (3) reward positive and significant impact on employee performance, (4) reward positive and significant impact on creativity, and (5) creativity positive and significant effect on employee performance.
Keywords: Work Environment, Reward, Creativity, Performance